Setting the media agenda: a study of the 2010 Sudanese presidential elections - Idid, Syed Arabi; Elawad, Saifeldin Hassan (IIUM Press, 2015)
This research investigates the influence of new media agendas on traditional news media according to the theoretical framework of intermedia agenda-setting during the 2010 Sudanese presidential elections. Upon applying content analysis, cross-lagged correlation analysis, and Rozelle-Campbell Baseline analysis, the paper provides evidence of intermedia agenda-setting in Sudanese media across a number of dependent variables. Sudanese newspapers influenced the agenda of Sudanese blogs whilst blogs have an increasing impact on the agenda of the newspapers. Our content analysis found that the agendas of socio-political blogs were strongly correlated with those of the newspapers. The findings also presented evidence of intermedia agenda-setting between socio-political blogs and citizen journalism.